Contrasting distribution and speciation of sedimentary organic phosphorus among different basins of the Baltic Sea. Issue 4 (3rd February 2023) - Rydin, Emil; Broman, Elias; Reitzel, Kasper; Lukkari, Kaarina; Hermans, Martijn; Kumblad, Linda; Karlsson, Magnus; Apler, Anna; Ek, Bo; Sjöberg, Per J. R.
Abstract: Recycling of phosphorus (P) from deoxygenated sediments perpetuates eutrophic conditions in parts of the Baltic Sea. Sedimentary organic P is a major source of dissolved P to the water column, but also a sink for permanent P burial. The mechanisms behind these two pathways are, however, largely unknown. Using new methods, we determined P in DNA and phospholipids, which are both found in all organisms. We also identified inositol phosphates that are particularly important in eukaryotes. Sediment cores were collected from contrasting basins in the Baltic Sea to study their relative contribution to the total P pool. We found high DNA‐P/phospholipid‐P ratios in surface sediments from the Bothnian Bay and Bothnian Sea. However, these ratios were low throughout profiles in euxinic Baltic Proper sediments. The elevated ratios present in sediments overlain by oxic bottom waters might indicate the presence of a microbial community stimulated by bioturbation, whereas the low DNA‐P/phospholipid‐P ratios in Baltic Proper sediments likely indicate an energy‐limited microbial community, typical to the "deep biosphere" environment. Inositol‐P was almost absent in euxinic Baltic Proper sediments that had a low total P amount compared to those in the other basins. We suggest that variability in the composition of sedimentary microbial communities among the Baltic Sea basins might cause differences in organic P forms that in turn affects its turnover.